Malezas en los arrozales de América Latina - Fuentes de Piedrahíta, Cilia L.; Osorio, Armando; Granados, Juan Carlos; Piedrahíta Castañeda, Wilson (International Center for Tropical Agriculture, 2010)
Weeds affecting rice fields in Latin America A botanical description is given of the 25 most important weed species affecting rice fields in Latin America, as well as their geographical distribution. A typical rice field can present up to 30 species of weeds, distributed in four groups: dominant (high density); secondary (intermediate density); infrequent; and rare. In the rice belt of Latin America and the Caribbean, 25 weed species (belonging to 12 botanical families) have been identified as the most frequent. The key to undertaking any weed control action in rice is to identify and study those species considered as weeds. Herbicide manufacturers, for example, should correctly recognize the species being controlled by their products.